PENGARUH KOMPENSASI, LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. STRATEGI INISIATIF MEDIA JAKARTA - Hendri Jopanda (Jurnal Manajemen, 2019)
This study aims to determine the effect of compensation, work environment, and work discipline on the performance of employees of PT. Media Initiative Strategy. Determination of the sample in this study using a sample of 46 respondents and this study uses multiple linear regression method. The results of this study indicate that partially compensation has a significant effect on the performance of employees of PT. Media Initiative Strategy with tcount 3.889> t table 1.682 and significant value 0.000 <0.05, work environment has a significant effect on the performance of employees of PT. Media Initiative Strategy with tcount of -3.447 <t table 1.682 and significant value 0.001 <0.05 and work discipline have a significant effect on the performance of employees of PT. Media Initiative Strategy with tcount of -3.237 <t table 1.682 and significant value 0.002 <0.05. While simultaneously showing that compensation, work environment, and work discipline simultaneously affect the performance of employees of PT. Media Initiative Strategy with Fcount 9.199> Ftable 2,827 and significant value 0,000 <0.05.